Suppression of lymphoma growth by the xenoestrogens bisphenol A and genistein - Yakimchuk, Konstantin (Endocr Connect, 2018)
Well-defined physiological functions of estrogens are mediated via nuclear estrogen receptors α (ESR1) and β (ESR2). With regard to hematological malignancies, expression of ESR2 has been found in both B and T cell lymphomas. In addition to endogenous estrogens or selective ESR2 agonists, ESR2 signaling may be affected by both environmental synthetic estrogen-mimicking compounds and dietary phytoestrogens. In the present study, we demonstrate that oral exposure with either the synthetic compound bisphenol A (BPA) or the dietary phytoestrogen genistein reduced the growth of grafted murine T cell (EG7) and human B cell (Granta-519 mantle cell) lymphomas which both express ESR2. Suppression of lymphoma growth was due to reduced proliferation (BPA and genistein) and induction of apoptosis (genistein). Inhibition of lymphoma growth was seen at a BPA dose of 50 µg/kg body weight (BW)/day considered to be safe human exposure dose or a genistein dose of 1 mg/kg BW/day orally, which is reached in soy-rich diets. Thus, our study indicates that the environmental xenoestrogens BPA and genistein have anti-proliferative effects on ESR2-expressing lymphomas. Our data suggest that phytoestrogens may be considered as a dietary supplement for lymphoma patients and possibly for prevention of lymphoid malignancies.